PENERAPAN MODEL PEMBELAJARAN BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN MEMBACA DESCRIPTIVE TEXT PADA SISWA KELAS X SMKS BUDI MURNI 3 JAKARTA - Setia, Uli Tri (Jurnal Analisis Pendidikan Sosial, 2025)
This study aims: 1) to obtain information about the effect of applying a model based learning based on the ability to read descriptive texts for students in class X SMKS Budi Murni 3 years. 2) In order to obtain information on how much students know descriptive texts after using a model problem-based learning for students in class X SMKS Budi Murni 3. Researchers use classroom action research, researchers take action to solve problems in the learning process in the classroom. Using descriptive research methods, because it gives an idea like a learning method used by researchers and what the expected learning outcomes can be achieved. The subjects of this study were students of Class X SMKS Budi Murni 3 with descriptive text material. From the results of this action, it can be shown that the teaching and learning process with a learning-based model has a good influence on improving student learning achievement. This is indicated by efforts to develop and assess students on the subject being taught. There is an increase in learning mastery from cycles I, II and III (89.29%). In cycle III students classically have been able to achieve complete learning.